Global convergence in leaf respiration from estimates of thermal acclimation across time and space. Issue 4 (21st April 2015) - Vanderwel, Mark C.; Slot, Martijn; Lichstein, Jeremy W.; Reich, Peter B.; Kattge, Jens; Atkin, Owen K.; Bloomfield, Keith J.; Tjoelker, Mark G.; Kitajima, Kaoru
Summary Recent compilations of experimental and observational data have documented global temperature‐dependent patterns of variation in leaf dark respiration (R), but it remains unclear whether local adjustments in respiration over time (through thermal acclimation) are consistent with the patterns in R found across geographical temperature gradients. We integrated results from two global empirical syntheses into a simple temperature‐dependent respiration framework to compare the measured effects of respiration acclimation‐over‐time and variation‐across‐space to one another, and to a null model in which acclimation is ignored. Using these models, we projected the influence of thermal acclimation on: seasonal variation in R; spatial variation in mean annual R across a global temperature gradient; and future increases in R under climate change. The measured strength of acclimation‐over‐time produces differences in annual R across spatial temperature gradients that agree well with global variation‐across‐space. Our models further project that acclimation effects could potentially halve increases in R (compared with the null model) as the climate warms over the 21st Century. Convergence in global temperature‐dependent patterns of R indicates that physiological adjustments arising from thermal acclimation are capable of explaining observed variation in leaf respiration at ambient growth temperatures across the globe.